2020
DOI: 10.1111/gfs.12496
|View full text |Cite
|
Sign up to set email alerts
|

Nitrous oxide emissions from grass–clover swards as influenced by sward age and biological nitrogen fixation

Abstract: Agricultural production systems affect the emissions of all major greenhouse gases (GHG), namely carbon dioxide (CO 2) (Freibauer, Rounsevell, Smith, & Verhagen, 2004), nitrous oxide (N 2 O) (Reay et al., 2012) and methane (CH 4) (Haque, 2018). The livestock sector alone has been estimated to contribute about 18% of the global anthropogenic GHG emissions (Haque, 2018). Projected increments in consumption of animal products will increase the challenge of balancing environmental concerns and food provision (Roja… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 66 publications
5
21
0
Order By: Relevance
“…White clover suffered only 6 weeks of drought. The range of dry matter yield observed in this study agrees with the 9-12 Mg ha −1 reported for similar grasslands under similar climatic and soil conditions, depending on the age or soil N status [43,45].…”
Section: Plant Yields Botanical Composition and Soil Residual Nsupporting
confidence: 89%
See 3 more Smart Citations
“…White clover suffered only 6 weeks of drought. The range of dry matter yield observed in this study agrees with the 9-12 Mg ha −1 reported for similar grasslands under similar climatic and soil conditions, depending on the age or soil N status [43,45].…”
Section: Plant Yields Botanical Composition and Soil Residual Nsupporting
confidence: 89%
“…The range of N uptake by the grasslands in this study appears to be on the upper side of the range of values (10-450 kg N ha −1 year −1 ) reported by Bessler et al [68]. It appears grass-legume swards are associated with the high N uptake, as corroborated in this study and by Reinsch et al [45]. This has been attributed to species complementarity evident by the development of high root length and root density by grass-legume species [69], leading to low PRN.…”
Section: Soil Mineral N Availability and Plant N Uptakesupporting
confidence: 87%
See 2 more Smart Citations
“…Field sampling was carried out at the Kiel University farm "Lindhof" close to the Baltic Sea (54°27′ N, 9°57′ E, elevation 10 m a.s.l.) [36]. The soil was sandy loam, classified as a Eutric Luvisol, with a texture composition of 11% clay, 29% silt, and 60% sand in the top 30 cm of soil [37].…”
Section: Study Areamentioning
confidence: 99%